Peluang dan Tantangan Profesi Advokat Bagi Alumni Program Studi Ahwal Syakhshiyah Fakultas Agama Islam UNISMA Bekasi - Jesi Aryanto (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2013)
The title of this article is "Opportunities and Challenges for Professionals Advocate the program of Ahwal al-Syakhshiyah graduates Unisma-Bekasi". In the descriptive analysis of this article can be seen that after the Reformation, the opportunities and challenges of the profession advocate greater Ahwal al- Syakhshiyah graduates, for example, the presence of legal institutions such as the Constitutional Court, the Commercial Court, the Ad Hoc Corruption Commission, the Judicial Commission and so is the container in which advocates can play a role. Similarly, the proliferation of Islamic financial institutions are in dire need of the role of the advocate, who not only understand the positive law but deep knowledge in the field of Islamic law (sharia). The opportunities of ahwal Syakhsiyah scholars in the advocacy world more open with the enactment of Law No. 18, 2003. Therefore, graduates should receive stock Ahwal Syakhshiyah scholarly depth. Furthermore, it should also have a high moral because in addition to chances is promising, the challenge is very large such as the proliferation of corruption involving many law enforcement agencies